MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SMA MELALUI TEKNIK PROBING – PROMTNG - Dewi Ananti Wulan; Ely Susanti; Nyimas Aisyah (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractThis research is aimed to increase students higher order thinking skill in mathematics learning using probing-prompting learning technique. This research is descriptive research with 21 students of X.C class at SMAN 02 Indralaya Utara as the subject. Learning process is according to the characteristic and steps of probing-prompting learning technique. Techniques for collecting data are test which includes of three problems and interview to obtain additional data. According to the results of research, it’s obtained that representation of students’ higher order thinking skill in problem based learning on X.C class at SMAN 02 Indralaya Utara is good with this details: percentage of students who have higher order thinking skill with category excellent is 19%. Then, 38,1% have higher order thinking skill with category good; 28,6% have higher order thinking skill with category medium; 14,3% have higher order thinking skill with category bad; nothing shave higher order thinking skill with category very bad. Indicator of analyzing have the highest percentage with 85,7%. Then, indicator of evaluating have percentage 71,4%, and indicator with the lowest percentage is creating with 44,6%.Keywords: Higher order thinking skill, probing-prompting technique